A comprehensive analysis towards the Fermi-LAT source 4FGL J1846.9–0227: jets of a protoplanetary nebula producing γ-rays? - Ortega, Martin Eduardo (2024)
Most of the γ -ray sources in the Fermi-LAT 14-yr source catalogue are associated with pulsars and blazars. However, unveiling the nature of the still unassociated γ -ray sources is important for the understanding of high energy emission mechanisms in astrophysical objects. This work presents a comprehensive study towards the region covered by the Fermi source 4FGL J1846.9 − 0227, previously suggested to be a blazar and a massive protostar. Using multiwavelength observations, we analysed several astrophysical objects in the region as possible counterparts of the Fermi-LAT source. Having discarded most of them after a detailed and comprehensive analysis, we suggest that the most likely candidate to be such a counterpart is IRAS 18443 − 0231, a likely protoplanetary nebula. We found that the radio continuum emission at 3 GHz of IRAS 18443 − 0231 shows a compact source related to faint emission with jet-like morphology. Additionally, we identified an associated redshifted CO molecular outflow. Using data from several catalogues, we obtained radio spectral index values ranging from − 0.57 to − 0.39 for IRAS 18443 − 0231, indicating synchrotron emission due to particles accelerated by the jets. We point out that these jets could explain the γ -ray emission through mechanisms such as proton-proton collisions and relativistic bremsstrahlung. IRAS 18443 − 0231, lying almost at the centre of the Fermi confidence ellipse and related to the hard X-ray source 4XMM J184700.4 − 022752, would be the first association between a protoplanetary nebula and γ -ray emission.